Study of factors of increasing the innovative activity of transport enterprises - Pererva, P. G.; Kersys, Robertas (Полтавський державний аграрний університет, 2024)
The results of the studies have shown that the availability of capital for investment in new technologies, research and development is a key factor. Transport enterprises with stable financial flows can afford innovative projects. Sufficient funding is needed to develop and implement innovative projects. Lack of funds may limit the adoption of new Technologies
Keywords: capital; new technologies; innovation; efficiency; industrial enterprises